Efektivitas Pembelajaran Bahasa Indonesia Dengan Google Classroom Terhadap Minat Baca Saat Pandemi Covid-19 - Ni Putu Agustina Damayanti (Jayapangus Press, 2021)
A pandemic period is a period of human transition the spread of diseases that can claim human lives. This is very influential on the nature, interaction, social, economy and affects the restriction of activities between humans in carrying out their mobility. It's spread able to influence activities in the world of education. Education as a medium for delivering knowledge with many can be students is indicated a place spread of covid-19 in the school environment. This problem greatly changed way teachers work in delivering learning to students, which used to be face-to-face, now online. The impact of pandemic on student learning at SD Negeri 4 Dauhwaru such as: students 'reading interest has decreased, students' desire to learn is reduced, tasks or homework are mostly done by their parents. These behaviors continuously ask for help with their duties. The method used in study use librarian research for theoretical studies, references and scientific literature related culture, values ​​and norms develop in social situation under study. The solution that can provided by the government tackling education in the midst of pandemic use online learning such as google classroom. This feature helps teachers in delivering material online without reducing the face-to-face feeling from teacher to student in Indonesian language learning. Learning Indonesian will be more optimally delivered face-to-face and more optimally for students catch. The use google classroom a medium for delivering material, assignments and quizzes for students is expected to be able provide better reading interest and enthusiasm for students during a pandemic.